Human papillomavirus (HPV) infection in a case‐control study of oral squamous cell carcinoma and its increasing trend in northeastern Thailand. Issue 6 (26th December 2016) - Phusingha, Pensiri; Ekalaksananan, Tipaya; Vatanasapt, Patravoot; Loyha, Kulchaya; Promthet, Supannee; Kongyingyoes, Bunkerd; Patarapadungkit, Natcha; Chuerduangphui, Jureeporn; Pientong, Chamsai
Abstract : Human papillomavirus (HPV) is an independent risk factor for development of oral squamous cell carcinoma (OSCC). This study aimed to investigate the role of HPV infection and the trend in percentage of HPV‐associated OSCC over a 5‐year period in northeastern Thailand. In this case‐control study, 91 exfoliated oral cell samples and 80 lesion cell samples from OSCC cases and exfoliated oral cells from 100 age/gender‐matched controls were collected. HPV infection was investigated by PCR using GP5+/GP6+ primers followed by HPV genotyping using reverse line blot hybridization. Quantitative RT‐PCR was used to evaluate HPV oncogene transcription. Temporal trends of HPV infection were evaluated in archived formalin‐fixed paraffin‐embedded (FFPE) OSCC tissues using in situ hybridization. HPV DNA was found in 17.5% (14/80) of lesion samples from OSCC cases and 29.7% (27/91) of exfoliated oral cell samples from the same cases. These values were significantly higher than in exfoliated oral cell samples from controls (13%, 13/100). HPV‐16 was the genotype most frequently found in OSCC cases (92.8%, 13/14 infected cases). Interestingly, HPV oncogene mRNA expression was detected and correlated with OSCC cases ( P < 0.005). Of 146 archived FFPE OSCC samples, 82 (56.2%) were positive for high‐risk HPV DNA and 64 (43.8%) cases were positive for HPV E6/E7 mRNA expression. There was a trend of increasing percentage of HPV‐associated OSCC from 2005 to 2010. This was especially so for females with well‐differentiated tumors in specific tongue sub‐sites. We suggest that HPV infection plays an important role in oral carcinogenesis in northeastern Thailand.